2019
DOI: 10.3390/app9235044
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of Reverse Osmosis (RO) Reject Water as a Mixing Water of Calcium Sulfoaluminate (CSA) Cement for Brick Production

Abstract: This study explored the possibility of using reverse osmosis (RO) reject water as a mixing water for producing cementitious bricks using calcium sulfoaluminate (CSA) cement along with gypsum, and it investigated the changes in the properties of CSA cement pastes when RO reject water was used. The results were compared with those obtained using purified water and seawater. Overall, the use of RO reject water improved the cement paste’s strength. Given that the use of RO reject water very slightly affected ettri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This high R 2 value suggests that the linear regression equation obtained is meaningful. In addition, the critical value of variance F 0.05 (4,5) of the regression equation is 6.256, and all variance values of the above formulas are larger than 6.256, so the obtained equation is significant.…”
Section: Regression Analysismentioning
confidence: 95%
See 2 more Smart Citations
“…This high R 2 value suggests that the linear regression equation obtained is meaningful. In addition, the critical value of variance F 0.05 (4,5) of the regression equation is 6.256, and all variance values of the above formulas are larger than 6.256, so the obtained equation is significant.…”
Section: Regression Analysismentioning
confidence: 95%
“…Five samples were prepared in each group, and the specimen was dried to a constant weight using an oven at 105 ± 5 • C, after which the volume (V) and dry weight (G 0 ) of the samples were measured by brick caliper and electronic scale, respectively. The bulk density was calculated according to Equation (4).…”
Section: Bulk Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…The reverse osmosis (RO) method is commonly used to purify water with high levels of salt, but it produces a large volume (38%) of rejected water with high levels of total dissolved salts (TDS) and other contaminants, such as toxic metals and organic pollutants [16][17][18]. The RO-rejected water (ROR) can be an environmental issue, i.e., because of the high TDS load of metals and organic and inorganic compounds [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…However, currently, there is a growing interest in researching the potential of reusing ROC. For example, Lee et al [23] demonstrated that ROC usage for brick production satisfied the Korean Standards F 4004 and toxicity characteristic leaching procedure; thus, it is recommended that ROC is used as mixing water to produce calcio sulfoaluminate cement bricks for use in construction. Rana et al [24] determined that ROC represents a non-toxic, cost-effective, and nutrient-rich growth media for algae cultivation.…”
Section: Introductionmentioning
confidence: 99%